2023
DOI: 10.51821/86.2.11547
|View full text |Cite
|
Sign up to set email alerts
|

Diet and non-alcoholic fatty liver disease, a short narrative review

Abstract: The growing importance of non-alcoholic fatty liver disease (NAFLD), the biggest non-communicable liver disease, inherently leads to an increased attention to lifestyle and diet that are closely intertwined with NAFLD. Elements of the Western diet such as saturated fats and carbohydrates and thus soft drinks, red meat and ultra-processed foods are linked to NAFLD. Contrarily, diets rich in nuts, fruits, vegetables and unsaturated fats as seen in the Mediterranean diet are linked to less prevalent and less seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…In accordance with such healthier food choices, women usually attached greater importance to health [ 36 ]. As in this study, the effects of oil intake have been shown to be associated with the development of steatosis, probably due to the intake in terms of calories, and positive effects due to the presence of polyphenols, such as oleuropein, hydroxytyrosol, tyrosol, and caffeic acid, which have important antioxidant and anti-inflammatory effects [ 37 ], while the consumption of red meat was predictive in the elderly, and the literature describes a higher risk of developing liver disease in subjects who consume more red meat [ 38 ]. Furthermore, the literature declares a neutral role of wheat consumption in the development of steatosis without investigating the age of the subjects [ 39 ], while with regard to the consumption of dairy products, there are conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with such healthier food choices, women usually attached greater importance to health [ 36 ]. As in this study, the effects of oil intake have been shown to be associated with the development of steatosis, probably due to the intake in terms of calories, and positive effects due to the presence of polyphenols, such as oleuropein, hydroxytyrosol, tyrosol, and caffeic acid, which have important antioxidant and anti-inflammatory effects [ 37 ], while the consumption of red meat was predictive in the elderly, and the literature describes a higher risk of developing liver disease in subjects who consume more red meat [ 38 ]. Furthermore, the literature declares a neutral role of wheat consumption in the development of steatosis without investigating the age of the subjects [ 39 ], while with regard to the consumption of dairy products, there are conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease and the more severe form of nonalcoholic steatohepatitis (NASH) are diseases where fat buildup in the liver can lead to cirrhosis and potentially fatal consequences. , There is currently a lack of understanding especially in terms of the molecular mechanisms of the disease . While it is known that diet plays a significant role, complex metabolic pathways can make it challenging to trace direct links between diet and resulting liver pathology .…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease and the more severe form of nonalcoholic steatohepatitis (NASH) are diseases where fat buildup in the liver can lead to cirrhosis and potentially fatal consequences. , There is currently a lack of understanding especially in terms of the molecular mechanisms of the disease . While it is known that diet plays a significant role, complex metabolic pathways can make it challenging to trace direct links between diet and resulting liver pathology . Fatty acids can be present both in the diet and in the liver, with the types and ratios being particularly significant to NASH progression, , and are emerging as therapeutic targets. , Understanding how fatty acids and other components cause and/or correlate with NASH is important, but there are few methods to map different biochemical components across the liver.…”
Section: Introductionmentioning
confidence: 99%
“…In the first review manuscript, Wilhelmus Kwanten (Antwerp University Hospital) offers practical advice for the management of patients with non-alcoholic/metabolic dysfunction-associated fatty liver disease (5). This makes sense for a disease that is mainly related to the metabolic context (6) and that is caused by dietary factors, which the author also describes (5). A dietary intervention therefore makes perfect sense (7), and the author provides real-life recommendations for daily practice (5).…”
mentioning
confidence: 99%
“…This makes sense for a disease that is mainly related to the metabolic context (6) and that is caused by dietary factors, which the author also describes (5). A dietary intervention therefore makes perfect sense (7), and the author provides real-life recommendations for daily practice (5). In the second manuscript, Anja Geerts (Ghent University Hospital) tackles a hot topic at the moment, namely the treatment of obesity and metabolic steatosis by metabolic surgery, and discusses potential pitfalls, notably the appearance of alcohol use disorder after surgery (8).…”
mentioning
confidence: 99%